2010
DOI: 10.4103/0974-1208.69341
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of pregnancy outcome in gonadotrophin-clomiphene combination vs clomiphene alone in polycystic ovarian syndrome and unexplained infertility-A prospective clinical trial

Abstract: OBJECTIVES:A large prospective clinical trial was conducted to compare the efficacy of single dose uFSH and clomiphene citrate combination with clomiphene citrate alone for ovulation induction to improve the pregnancy rate.MATERIALS AND METHODS:The study was a randomized, prospective clinical trial. Totally, 1527 infertile women (4381 cycles) with polycystic ovarian syndrome (PCOS) (n=911/2573 cycles) and unexplained infertility (n=616/1808 cycles) were randomized into two groups. Group A received single dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Mukherjee S et al, reported that group A (uFSH +CC) had PR of 11% compared to 6.3% of group B (CC alone) in couples with unexplained infertility. 19 Gupta K et al, in their study observed higher pregnancy rate of 20% in CC+HMG group as compared to pregnancy rate of 15% in letrozole group. 15 In a similar study to the present study Chung MT et al, reported pregnancy rate of 14.8% in group 1(150U rFSH+CC) as compared to 20.4% in group 2(100U rFSH +CC).…”
Section: Discussionmentioning
confidence: 86%
“…Mukherjee S et al, reported that group A (uFSH +CC) had PR of 11% compared to 6.3% of group B (CC alone) in couples with unexplained infertility. 19 Gupta K et al, in their study observed higher pregnancy rate of 20% in CC+HMG group as compared to pregnancy rate of 15% in letrozole group. 15 In a similar study to the present study Chung MT et al, reported pregnancy rate of 14.8% in group 1(150U rFSH+CC) as compared to 20.4% in group 2(100U rFSH +CC).…”
Section: Discussionmentioning
confidence: 86%
“…The primary outcome measures in this trial were the biochemical and clinical pregnancy rates. On the basis of previous studies, 14 94 participants were required in each group to detect this difference with a 5% level of significance (α error=0.05) and 80% power (1−β=0.8).…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that the addition of single dose of uFSH improves pregnancy outcome particularly in anovulatory infertility (WHO II) compared with CC alone. However, they admitted the need for more RCTs to conWrm the possibility of replacing CC as the Wrst-line therapy for PCOS with CC + uFSH [82].…”
Section: Day 3 Ufsh Protocolmentioning
confidence: 98%
“…A recent large prospective clinical trial was conducted to compare the eYcacy of single dose uFSH (75 IU) on day 3 of menstrual cycle along with CC versus CC alone as a Wrst-line treatment in 1,527 infertile women (4,381 cycles), including PCOS (n = 911; 2,573 cycles) and unexplained infertility (n = 616; 1,808 cycles) [82]. Pregnancy and miscarriage rates were compared between groups.…”
Section: Day 3 Ufsh Protocolmentioning
confidence: 99%